Thermal management in high power devices using diamond - Kyatam, Shusmitha (2023)
The demand for high-performance electronic devices has led to increase in power dissipation as well as heat flux at the device level. Concurrently the requirement to achieve a smaller form-factor and lower device operating temperatures is compounding the thermal challenge. Thermal design for an electronic device can no longer be treated as trivial issue. Power and performance trade-offs and innovative circuit-design techniques are required to reduce power consumption as well as improving the efficiency of the devices. In order to reduce the thermal resistance new materials and process improvements in packaging and heat-sink technology are essential. It is also critical to ensure the cost, viable thermal design and form factor during the design and development phases. At the present moment, the main limitation is no longer the lithography capability to handle smaller and smaller devices, but the problem of thermal management inside chips with billions of devices switching between on and off states. In order to avoid the malfunctions of electronics and to ensure the reliability and efficiency of the electronic systems, substantial research work has been done to explore highly effective cooling techniques to keep up with the development pace of new and larger electronic equipment. The thermal management process involves the technology of generation, control and dissipation of the heat in electronic devices and systems. The major challenges in thermal management can be analyzed by the study of heat dissipation in electronic devices, which vary from 5 W/cm² on a PCB to 2000 W/cm² for a semiconductor laser. The need for novel cooling solutions has become a problem of paramount importance. The effective process of managing heat depends on how well the heat transfer mechanisms are integrated into each level of electronic packaging. This includes the device, board and system levels. While there are many different thermal devices and design strategies that can be used, they generally fall into two categories namely passive or active thermal management. Passive thermal management refers to cooling technologies that rely solely on the thermodynamics of conduction, convection and radiation to complete the heat transfer process. These are the most common cooling methods in use, because they are the least expensive and the easiest to implement. Active thermal management refers to cooling technologies that must introduce energy which is typically an external device to enhance the heat transfer process. Understanding how energy is lost as heat transferred to the environment is also an open issue, given that most of the available circuit theoretic tools are not able to merge circuit analysis and thermodynamics in the same frame.The proposed PhD work, investigates the use of diamond in various electronic cooling techniques both at device and circuit assembly i.e. PCB/Board levels. The research work will concentrate on the effects of temperature and temperature dependent modelling of power electronic devices. It also focuses on design and analysis of High-k diamond layer in fabrication of LEDs and PICs. The theoretical work will be complemented with simulation and experimental work, which includes electronic cooling techniques at different scales. Firstly, at the device level, the feasibility of using a diamond chip carrier is investigated and evaluated its impact on the characteristics of power LEDs. Secondly at the assembly level, analyzed the use of diamond plates as holders for PICs and studied effects such as thermal crosstalk between DFB lasers and other passive cooling techniques. The use of diamond PCBs for 3×3 LED arrays is also proposed and compared with conventional MCPCB. This research pushes the boundary further towards more functionality in a smaller form factor for electronic products.